JOSt WATANABE: ANCESTRAL VISIONARY AND BCOLOGICAL WORLDVIEWINSIDE HIS CREATIVE PROCESS - Sauter, Silvia (2010)
José Watanabe, a charismatic and recognized poer beca use of the limpid articulation ofhis verses and his unseen wisdom, unites h.is talent and personal creativity or psychologicalwith another deeper process, in a visionary or impersonal way, which genesisapproaches to the profound inquiry resulting from a cognitive distinct process, transor impersonal, archetypal or primordial, even though common to humaniry, but for·gotten today-except tOr some scientists, shamans, rnystics, p(r)o(ph)ets or visionariesable ro access chis field. This way of petception succeeds in mediating between rheimpersonal reahn of rhe collecrive unconscious and the contetnporary imaginary. Eachof Watanabe's poems is an epiphany, Rosella di Paolo synthesizes, "a strike of light,rhe sudden perception of an angle of realiry snarched from darkness and silence." TI1ecreatlon thus germinated is immediate, different and transgressive tOr its lüstorícal moment:it is rare and Ü1.scinating at once; its imagery tends to awake communal elementsdeeply buried, which if rhey remain buried, will burst inhumanly. This double visionnourished by the poer's practical maternal wisdom and culntral psychic sensibiliry, ofa father's who used toread and translate haikus ro him, that taught him to grasp rheessential on a direct way, primordial or archetypal manner which often makes the interpretarlonof thls poetry difficult. Some of Watanabe's verses, because oÍ its samesoberness cause resonances of something distant or disregarded. His poetry offers anecological perception that even when it appears candid, from surroundings that weconstanrly ignore or disparage.